The Development of HOTS-Based Encyclopedia SAKU Book to Enhance Science Literacy Culture in Thematic Learning - Anik Twiningsih; Ruth Karsini (LPPM Universitas Terbuka, 2025)
The culture of scientific literacy is being urgency in the 21st-century education challenges. 21st-century learning is inseparable from the textbooks used by students. This type of learning tool affects the interest of students in learning participation. The development of the HOTS-based encyclopedia SAKU book in this study is one of the researcher' efforts to enhance the culture of scientific literacy following the demands of 21st-century education. SAKU is an acronym for